2020
DOI: 10.1021/acs.jced.0c00319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Chloride and Lithium Bromide on the Phase Behavior of a Citrate–Polyethylene Glycol 2000 Aqueous Two-Phase System

Abstract: Several studies have shown that aqueous two-phase extraction using an aqueous two-phase system (ATPS) is a promising purification technology for biomolecules (e.g., monoclonal antibodies). To beneficially influence the partitioning of the target biomolecule, a displacement agent can be added to the ATPS. Within this work, the influence of the displacement agents, sodium chloride (NaCl) and lithium bromide (LiBr), on the phase behavior of two ATPSs containing triammonium citrate and polyethylene glycol 2000 (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Wessner et al used NaCl and LiBr to study the ATPS of PEG 2000 –citrate salts at room temperature and specific pHs. It was observed that the addition of NaCl and LiBr salts increased and decreased the length of the tie-lines, respectively …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wessner et al used NaCl and LiBr to study the ATPS of PEG 2000 –citrate salts at room temperature and specific pHs. It was observed that the addition of NaCl and LiBr salts increased and decreased the length of the tie-lines, respectively …”
Section: Introductionmentioning
confidence: 97%
“…It was observed that the addition of NaCl and LiBr salts increased and decreased the length of the tie-lines, respectively. 34 Studies of the ATPSs of PEG + sulfate salts + water have also received extensive attention in the separation processes. Pirdashti et al measured the effect of the polymer molecular mass, pH, and temperature on the phase equilibrium of ATPSs of the ternary systems of PEG 2000 , PEG 3000 , and PEG 8000 + zinc sulfate or ammonium sulfate + water at T = 298.15, 303.15, and 308.15 K. The results proved that the two-phase region has been extended by increasing the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…To test the performance of an ATPS in enhancing the mass transport of target molecules for capture on detection surfaces of bioassays, we aimed to improve the sensitivity of a SiMREPS assay of a cancer-related DNA mutation using an ATPS composed of PEG (average molecular weight, MW ∼ 3350 Da), sodium citrate, and sodium chloride to enrich the target molecules in a small volume near the assay surface during the capture step. In the PEG-citrate ATPS, a second salt, sodium chloride, is added to enhance the partitioning of nucleic acids into the salt-rich phase . First, to better understand what bulk compositions would promote the formation of an ATPS, a binodal curve with a constant mass of sodium chloride and varying PEG (MW 3350) and sodium citrate was measured using the cloud-point titration method (Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The replacement of traditional catalytic processes by enzymatic approaches, together with the surge in the use of biopharmaceuticals such as antioxidant-rich food supplements and monoclonal antibodies, has been increasing the demand for biomolecules and sharpening the need for more sustainable and cost-effective methodologies concerning their extraction . However, biomolecules are extremely sensitive to factors such as temperature, ionic strength, interfacial stress, and pH, so the operative conditions of extractive processes must be optimized to avoid denaturation, sterilization, and loss of activity, and to control the characteristic lability of these species …”
Section: Introductionmentioning
confidence: 99%
“…The replacement of traditional catalytic processes by enzymatic approaches, together with the surge in the use of biopharmaceuticals such as antioxidant-rich food supplements 1 and monoclonal antibodies, 2 has been increasing the demand for biomolecules and sharpening the need for more sustainable and cost-effective methodologies concerning their extraction. 3 However, biomolecules are extremely sensitive to factors such as temperature, ionic strength, interfacial stress, and pH, so the operative conditions of extractive processes must be optimized to avoid denaturation, sterilization, and loss of activity, and to control the characteristic lability of these species. 4 One of the biggest challenges for the extraction and purification of biomolecules such as amino acids, enzymes, antioxidants, hormones, antibodies, and vitamins is the preservation of their bioactivity and intrinsic value (biocompatibility), which makes processes with green solvents and mild extractive conditions almost mandatory.…”
Section: Introductionmentioning
confidence: 99%